2016
DOI: 10.1038/sc.2016.99
|View full text |Cite
|
Sign up to set email alerts
|

Modular control of gait after incomplete spinal cord injury: differences between sides

Abstract: The analysis of muscle synergies shows potential to detect differences between the two sides in patients with iSCI. Specifically, the VAF may constitute a new neurophysiological metric to assess and monitor patients' condition throughout the gait recovery process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…By comparing these muscle synergies, we can assess gait symmetries of patients. Although the usual method for previous studies to assess the performance of stroke patients is to compare them with healthy subjects (Bowden et al, 2010 ; Gizzi et al, 2011 ; Routson et al, 2013 ; Hayes et al, 2014 ; Barroso et al, 2016 ; Pérez-Nombela et al, 2017 ), we show that lateral symmetry can still be used as a relative measure by comparing the sides of the patients. Future considerations would be to analyze healthy subjects to test the accuracy of this method.…”
Section: Discussionmentioning
confidence: 69%
“…By comparing these muscle synergies, we can assess gait symmetries of patients. Although the usual method for previous studies to assess the performance of stroke patients is to compare them with healthy subjects (Bowden et al, 2010 ; Gizzi et al, 2011 ; Routson et al, 2013 ; Hayes et al, 2014 ; Barroso et al, 2016 ; Pérez-Nombela et al, 2017 ), we show that lateral symmetry can still be used as a relative measure by comparing the sides of the patients. Future considerations would be to analyze healthy subjects to test the accuracy of this method.…”
Section: Discussionmentioning
confidence: 69%
“…There are several examples of studies employing factorization of EMG activity to study human locomotion. For several reasons, the most widespread locomotion type that has been studied is walking ( Ivanenko et al, 2004 ; Cappellini et al, 2006 ; Courtine et al, 2006 ; Clark et al, 2010 ; McGowan et al, 2010 ; Dominici et al, 2011 ; Allen and Neptune, 2012 ; Bolton and Misiaszek, 2012 ; Chvatal and Ting, 2012 , 2013 ; Lacquaniti et al, 2012 ; Oliveira et al, 2012 ; Rodriguez et al, 2013 ; Barroso et al, 2014 ; Maclellan et al, 2014 ; Routson et al, 2014 ; Coscia et al, 2015 ; Gonzalez-Vargas et al, 2015 ; Hagio et al, 2015 ; Licence et al, 2015 ; Martino et al, 2015 ; Nazifi et al, 2015 ; Tang et al, 2015 ; Buurke et al, 2016 ; Gui and Zhang, 2016 ; Kim et al, 2016 ; Lencioni et al, 2016 ; Meyer et al, 2016 ; Pérez-Nombela et al, 2016 ; Yokoyama et al, 2016 ; Allen et al, 2017 ; Janshen et al, 2017 ; Santuz et al, 2017a ; Shuman et al, 2017 ; Saito et al, 2018 ). Due to the easiness of examining this slow-speed type of locomotion, it is not a surprise that the majority of studies use walking as the main object of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether for computational or neurophysiological reasons, some studies found consistency in the recruitment of the same motor primitives and/or modules across varying velocities ( Ivanenko et al, 2004 ; Cappellini et al, 2006 ; Routson et al, 2014 ; Buurke et al, 2016 ; Gui and Zhang, 2016 ), while others found walking-, running-, and/or velocity-specific sets of motor primitives and/or modules ( Cappellini et al, 2006 ; Routson et al, 2014 ; Coscia et al, 2015 ; Gonzalez-Vargas et al, 2015 ; Yokoyama et al, 2016 ). The role of muscle synergies for locomotion in pathology has been a focus of a few groups in recent years ( Latash and Anson, 2006 ; Clark et al, 2010 ; Giszter and Hart, 2013 ; Rodriguez et al, 2013 ; Routson et al, 2014 ; Coscia et al, 2015 ; Tang et al, 2015 ; Falaki et al, 2016 ; Lencioni et al, 2016 ; Meyer et al, 2016 ; Pérez-Nombela et al, 2016 ; Shuman et al, 2016 , 2017 ; Wenger et al, 2016 ; Allen et al, 2017 ; Banks et al, 2017 ). Given the simplification in presenting the data due to the dimensionality reduction, it is appealing to think to a possible clinical application of the method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, abnormal muscle synergy patterns have been widely reported in post-stroke survivors during locomotion [18], arm isometric contractions [19], and voluntary reaching movements [20]- [23]. Muscle synergies have also been explored in subjects with spinal cord injury, revealing substantial differences to healthy individuals during different motor tasks: hand grip function [24], different locomotor tasks in children [25], postural balance [26], [27], gait [28], and standing protocols under spinal cord stimulation [29]. All this evidence supports that muscle synergies can be a powerful tool for characterizing motor behavior and providing physiological markers to assess motor function in injured patients.…”
Section: Introductionmentioning
confidence: 99%